The Effect of Rice Self-Sufficiency on Farmers' Welfare in Indonesia: A Dynamic Panel Data Approach: BPS, Institut Pertanian Bogor (Jurnal Ekonomi dan Kebijakan Pembangunan, 2024)
For decades, Indonesia has implemented a rice self-sufficiency policy aimed at increasing domestic rice production and reducing imports. However, claiming that rice self-sufficiency will benefit farmers is questionable because farmers' characteristics have not changed significantly over the past 50 years. This study aims to evaluate the effect of achieving rice self-sufficiency on farmers' welfare. The difference-GMM method of estimation, which accommodates potential endogeneity issues, is the best choice for explaining the model. Regression results show that the only significant variable in the model is the price producer variable. However, increasing the price cannot easily occur due to the asymmetric characteristics and inefficiencies in the rice supply chain. Therefore, government policy is insufficient to improve farmers' welfare. Furthermore, rice cultivation appears to benefit middlemen, wholesalers, and retailers, rather than small farmers. The ratio between trade margins and farmers' share in rice markets is always 30% for farmers and 70% for margin traders for many year. This result is also supported by the statistically insignificant level of rice self-sufficiency in improving the farmers' terms of trade in the food crop sub-sector.. Increasing efficiency and productivity through subsidies and technology adoption by farmers become crucial solutions to improve farmer welfare.